The Protection of Privacy in the Workplace: A Comparative Study - Gondwe, Mimmy (Stellenbosch University, 2011)
The importance of privacy lies in the fact that it represents the very idea of human dignity or the preservation of the ‘inner sanctum’. Not surprisingly, however, operational concerns of employers and technological developments combine continuously to challenge the preservation of privacy in the workplace. Employees the world over are exposed to numerous privacy invasive measures, including drug testing, psychological testing, polygraph testing, genetic testing, psychological testing, electronic monitoring and background checks. Hence, the issue at the heart of this dissertation is to determine to what extent privacy is protected in the South African workplace given advancements in technology and the implications (if any) for the right to privacy as such. A secondary aim of the dissertation is to attempt to provide a realistic balance between the privacy concerns of employees and the operational needs of employers in this technological age. As such the main focus of dissertation falls within the sphere of employment law. In order to provide an answer to the research issue discussed above, the dissertation addresses five ancillary or interrelated issues. First, the broad historical development of the legal protection of privacy is traced and examined. Second, a workable definition of privacy is identified with reference to academic debate and comparative legislative and judicial developments. Third, those policies and practices, which would typically threaten privacy in the employment sphere are identified and briefly discussed. Fourth, a detailed evaluation of the tension between privacy and a number of selected policies and practices in selected countries is provided. More specifically, the dissertation considers how these policies and practices challenge privacy, the rationale for their existence and, if applicable, how these policies and practices – if necessary through appropriate regulation – may be accommodated while simultaneously accommodating both privacy and the legitimate concerns of employers. The selection of these practices and policies is guided by two considerations. At the first level the emphasis is on those challenges to privacy, which can be traced back to technological developments and which, as such, foster new and unique demands to the accommodation of privacy in the workplace. The secondary emphasis is on those policies, which are representative of the fundamental challenges created by new technologies to privacy. To effectively address the above issues the dissertation uses the traditional legal methodology associated with comparative legal research, which includes a literature review of applicable law and legal frame work and a review of relevant case law and a comparative study of selected foreign jurisdictions.
URI: http://hdl.handle.net/10019.1/17849
Keywords: Privacy infringements; Privacy protection; Right of privacy

Aspects of the nature and online resolution of domain-name disputes - Hurter, Eddie (University of South Africa, 2011)
The thesis analyses selected aspects of domain-name law, mainly from the perspective of trade-mark law. It discusses the evolution of the domain-name system and how it operates as background to a more detailed discussion of the theoretical classification of domain names. The thesis then examines the interplay between trade marks and domain names, and the resolution of domain-name disputes resulting from the inherent tension between these two systems. The main principles of domain-name dispute resolution are identified by way of an analysis of the panel decisions handed down in terms of the international Uniform Dispute Resolution Policy (UDRP) and the South African domain name dispute resolution regulations. This analysis always addresses, too, the extent to which national trade-mark law principles (with reference to the laws of South Africa, the United Kingdom, and the United States of America) apply, and the extent to which this is appropriate.
Keywords: Abusive domain name registration; Cybersquatting; Dispute resolution; Domain names; ICANN; Intellectual property; Internet Corporation for Assigned Names and Numbers; Internet domain names; Nominet Dispute Resolution Service; Trademarks; Typosquatting; WIPO domain name processes; Well known trade marks; World Intellectual Property Organization

Culture of international arbitration and the evolution of contract law - Karton, Joshua David Heller (University of Cambridge, 2011)
Keywords: Arbitrage; Arbitragem; Arbitration; Contract law; International Arbitration

Public employment and the relationship between labour and administrative law - Loots, Barbara Evelyn (University of Stellenbosch, 2011)
The focus of this study is the rights-based normative overlap of labour and administrative law in public employment. As the judiciary appeared to be unable to agree on a unified approach to the application of the rights to fair labour practices and just administrative action to public employment, it was clear that the complexity and multi-dimensional character of the debate required analysis of existing approaches to the regulation of the public employment relationship. The following initial research question was formulated: To what extent does (and should) the constitutionalised rights to fair labour practices (s 23) and just administrative action (s 33) simultaneously find application in the regulation of public employment relationships? In answering this question, certain realities had to be acknowledged, the most important being that the debate in question jurisprudentially revealed itself to be a jurisdictional turf-war between the Labour and High Courts, rather than proper consideration of the relevant substantive arguments and underlying normative considerations. This called for an additional dimension to be added to the research question, namely consideration of the extent to which the ss 23 and 33 rights are informed by variable and possibly different normative principles and whether these rights allow for cooperative regulation of public employment in accordance with the doctrine of interdependent fundamental rights. This became the primary focus of the study. In an attempt to simplify the debate, a deliberate decision was taken to limit the scope of the normative study to South Africa with its own historic influences, structures and constitutional considerations. The study shows that both labour and administrative law (as constitutionally informed) share concern for equity-based principles. This is evident from the flexible contextually informed perspectives of administrative law reasonableness in relation to labour law substantive fairness, as well as a shared concern for and approach to procedural fairness. Once simplified, and in the absence of any undue positive law complexity, the public employment relationship, at both a normative and theoretical level, furthermore shows no substantive status difference with private employment relationships. It is, however, accepted that there are job and sector-specific contextual differences. In the absence of substantive normative conflict between these branches of law and in the absence of a fundamental (as opposed to contextual) difference between public and private employment, there appears to be no reason to ignore the constitutional jurisprudential calls for hybridity, otherwise termed the doctrine of interdependence. The idea of normatively interdependent rights expresses the Constitution’s transformative vision (through the idea of flexible conceptual contextualism) and recognises that human rights may overlap. This also means that where such overlap exists, rights should be interpreted and applied in a mutually supportive and cooperative manner that allows for the full protection and promotion of those rights. In giving expression to the interdependent normative framework of constitutional rights, these norms (absent any substantive rights-based conflict) should then be used by the judiciary as an interpretative tool to align specific labour law and general administrative law in the regulation of public employment relationships.
URI: http://hdl.handle.net/10019.1/6683
Keywords: Administrative law; Employment law; Labour law

The external relations of company groups in South African law : a critical comparative analysis - Stevens, Richard Arno (University of Stellenbosch, 2011)
Groups of companies are part of the realities of the modern economic system. Despite the fact that such groups often function as a single economic entity, the legal point of departure remains that each company within the group of companies is a separate juristic person. The result of this is that a creditor of a company within the group can, in principle, only enforce his claim against the company which he contracted with or which caused him harm. Should he wish to claim from the holding company or other solvent companies within the group, he would have to rely on an exception to the doctrine of separate juristic personality, viz the possibility of piercing the socalled corporate veil. This dissertation is a comparative study of the extent to which the law protects a creditor of an insolvent company within a group. The applicable laws of Australia, Germany, New Zealand, the United Kingdom and the United States of America, were investigated and compared to the South African position. The dissertation concludes that the South African legal treatment of the problem is unsatisfactory and that the law should be amended through appropriate legislation.
URI: http://hdl.handle.net/10019.1/6883
Keywords: Company groups; Creditors; South African companies; South African law

Nigeria, oil and gas exploration and the Niger delta question : a study in corporate social responsibility - Bribena, E. K. (North-West University, 2011)
This thesis addresses issues of the Niger Delta question which represents one of the most intractable sources of socio-political destabilization in the Niger Delta region of Nigeria. The study is on the intricate dynamics amongst the Nigerian state, the transnational oi l corporations, the oil producing communities and the insurgent militia conflict. It investigates and explicates the "paradox of plenty" and the "resource curse", the "absentee government" and "state capture" and the debilitating effects of petroleum politics in Nigeria. The economic exploitation of the Niger Delta region's vast crude oil reserves by transnational oil corporations and government authorities is juxtaposed with the spectre of environmental degradation, human rights violations, and the recurrent rule of impunity. The protracted problems of the Niger Delta region thus, provide us with a pertinent analytical and contextual framework for the study of the dynamics and issues of transparency in other African petro-dollar states. It is argued in this study that the Niger Delta crisis is a conflict of values and fight for resources arising from decades of unacceptable standards of oil exploration and the absentee character of the Nigerian State. By its very nature, the study called for a qualitative approach, supplemented by unstructured interviews using aide memoirs with selected officials, on the basis of their innate knowledge of the subject matter. The legal comparative research method, with a historic component also played an integral role in this study. Some key findings and conclusions: 1. The study found that the Niger Delta crisis graduated from mère political agitations for state creation and provision of social amenities to extreme acts of hostage-taking and a twist of violence as a result of treating a major problem affecting the development of the Niger Delta people with levity for too long a period. 2. The study found that the on-going crisis in the Niger Delta region of Nigeria is a conflict of values and fight for resources amongst the oil-bearing people of the Niger Delta, transnational oil corporations and the Nigerian Government. 3. The study established some causal nexus between oil and poverty; oil and corruption; and, oil and human rights abuses. 4. That, the Niger Delta crude oil conflict is essentially a manifestation of state capture and inertia on the part of the Nigerian Government. 5. The study found that the Niger Delta economies are "criminalized" and are often characterized by conditions of anarchy and impunity. And this disorder is embedded in the dynamics of resource extraction, the nature and role of "shadow" state actors, as well as the interplay and patterns of relationships between organized criminal syndicates and the transnational oil corporations in the host communities. The study recommends, inter alia: I. That steps be taken by government to re-define its philosophy of national economic development from a state-driven to citizens-driven philosophy. To this end, Nigeria must seek to develop by developing its citizens, the aggregate of whose satisfactory living conditions should form the criteria for measuring national development. II . That effort must be made to steer the nation towards proper fiscal federalism. The present "food is ready" economy whereby federating units are enslaved to national "cake sharing" instead of value generation, discourages entrepreneurship and sustainable development. It promotes undue dependency on petroleum products, inequity and ethnic distrust. Ill. That Nigeria needs productive resource control, not just development in the sense of house and bridge building. What is needed is a noticeable leap in the standard of living in the Niger Delta. Thus, people and not federal accounts must be the object of improvement. IV. It is recommended that government should ensure robust, independent and co-ordinated oversight of the oil industry including its impact on human rights. V. Transnational oil corporations should undertake full corporate social responsibility and comprehensive assessment of the social and human rights impacts of all oil and gas projects, ensuring that adequate information is provided to affected individuals and communities and that the process is transparent. VI. It is strongly recommended that an Oil Pollution Liability Trust Fund should be established by the Federal Government in concert with oil companies. The fund will be made up of a percentage of tax levied on oil companies and a percentage of earnings of the Federal Government from oil. The fund should be used in ameliorating the conditions of the impacted environment and people. It is hoped that these findings and recommendations will go a long way in the quest for significant environmental and social improvements in the Niger Delta region of Nigeria.
Keywords: CSR; Corporate Social Responsibility; Nigeria; Petroleum industry and trade

Common good and the concept of expropriation in international law on foreign investment: Determinacy of substance in legitimacy of structure - Falsafi, Alireza (McGill University, 2011)
This thesis, exploring the rule of law for international rules, offers a human bond of common good between determinacy of substance and legitimacy of structure of rules in order to evaluate international obligations of States in international law on foreign investment. In an in-depth exposition of the theoretical underpinnings and practices underlying the normative structure of rules in international law, the thesis critically questions the legal reasoning embedded in—and the authority of rules borrowed from—principles and precedents or moral and political evaluations by arbitrators in interpretation of States' contractual, customary, and treaty obligations in investment arbitrations. With crucial moral, political, social and economic ramifications for the constitutional functions of States and concomitant interests of their human members implicated in the concept of expropriation in international law, the thesis provides a framework of legitimacy in a common good approach with structural criteria of recognition and coherence for the interpretation of States' obligations in investment arbitration. Coherence brings to the fore conflicting demands of justice requiring fresh evaluation divesting a general rule of its authoritative force, and recognition brings to the fore the validation of the power to engage in moral and political evaluation. Together, these structural criteria offer a common good approach of legitimacy to test the authority of States' obligations and the power of arbitrators in hard cases. By virtue of these criteria, the thesis characterizes the nature of substantive property rights of corporations and corresponding obligations of States in foreign investment as contingent and consensual in contrast with the absolute and constitutional rights of human beings in human rights. Through coherence and recognition, the thesis also portrays a supreme status for customary international law for the normative structure and substance of States' contractual or treaty obligations in the interpretation of hard cases in international law on foreign investment. The thesis espouses a new horizon for legal reasoning in foreign investment arbitration that eschews the lex lata veneer for lex ferenda propositions manufactured from precedents and principles, on the one hand, and the sheen of law for the conception of justice of investor-State arbitrators, on the other, in cases of hard confrontation between the demands of justice.
https://escholarship.mcgill.ca/concern/theses/dv13zz300
Keywords: Expropriation; Foreign investment; International law

Copyright in the digital environment : ontologies of copyright and digital works - Filippi, Primavera De (European University Institute, 2011)
The advent of Internet and digital technologies has radically transformed the way information is being produced and consumed. The consequences for copyright law are twofold. While digital media provide new opportunities for authors to produce and disseminate their works to the public, they simultaneously encourage and facilitate copyright infringement. Traditionally, in order to ensure compliance with the law, the copyright regime could rely upon the properties of physical media to constitute a natural barrier against copyright infringement. As the medium went digital, however, its properties became a catalyst for infringement. Designed for the physical world, the structure of the copyright does not adequately address the issues inherent to digital media. Private regulation therefore came into play in order to resolve the problem. While restrictive licensing agreements combined with technological measures of protection purport to reestablish a technological barrier against copyright infringement, permissive licenses such as Creative Commons purport to reduce the scope of protection granted by default under the law. Although differing in method, these approaches share a common goal: to realign the properties of the work with the properties of the digital medium by readjusting the legal attributes and technical characteristics of digital copies. As a legal concept, however, the notion of a copy must be precisely defined. After performing an ontological analysis of the copyright regime within the scope of the Functional Requirements for Bibliographic Records and the Information Artifact Ontology, the research concludes that physical copies fundamentally differ from their digital counterpart. While the former qualify as a token, the latter qualify as a class that is capable of multiple instantiations. Moreover, given that the identity of a digital copy can no longer be defined by its physical characteristics, it is fundamentally for the copyright license to determine the scope of the copy to which it refers.
Keywords: Copyright; Digital media; Electronic data processing; Intellectual property; Internet

The effects of state succession on cultural property : ownership, control, protection - Jakubowski, Andrzej (European University Institute, 2011)
The purpose of this study was to investigate the legal effects of state succession on cultural property. This is not a new topic of international law. Indeed, the attempts to provide a legal framework for the cultural aspects of state succession have been undertaken in international practice and legal scholarship since at least the mid-nineteenth century. Initially, these were strictly bound to the origin of the European nation-state, determining its territorial boundaries accordingly to ethnic and cultural divisions. However, the concept of cultural property in international law has evolved towards a broader, more human-oriented idea of cultural heritage. Such a conceptual shift has occurred in the last fifty years, marked by the gradual recognition of the fundamental role performed by cultural manifestations in the preservation of human dignity and the continuous development of all mankind. This study discusses to what extent the practice and the theory of state succession reflect this evolution. It attempts to reconstruct the principles regulating interstate arrangements with regard to such matters, contextualizing them in a broad historical and geographical framework. Particular attention has been paid to the question of state succession to international cultural heritage obligations. This piece of work explores their content, sources and status in state succession. It explains that nowadays the preservation and enjoyment of cultural heritage do not constitute the exclusive concern of state sovereignty. On the contrary, such values are of general interest to the international community as a whole. Therefore, the study advocates a new doctrinal approach, based both on the principles of international cultural heritage law and human rights law. This implies the limitation of the contractual freedom of states in the matter of cultural agreements, in favour of the continuity of international cultural heritage obligations in cases of state succession. Finally, the study proposes a list of guiding principles relating to the succession of states in respect of tangible cultural heritage, which may contribute to the further development of international practice.
Keywords: Cultural property; Property protection; State succession

Reformulating corporate residence: a coherent response to international tax avoidance - Loomer, Geoffrey (University of Oxford, 2011)
This thesis analyzes the concept of corporate residence, with particular reference to the law in the UK and Canada. It explores why corporate residence is relevant in tax policy, how corporate residence is understood in law, and how revenue authorities respond to the use and alleged 'abuse' of residence rules. Part I argues that the residence of taxpayers generally (individual or corporate) remains a relevant factor in international tax design, that taxation of corporations on the basis of residence has some justification, but that there is a disjunction between meaningful residence-based taxation and current definitions of corporate residence in domestic law and tax treaties. The formulations of residence based on incorporation, central management and control, and place of effective management, particularly as applied to multinational enterprises, are considered and are found to be deficient. Part II critically analyzes the major policy responses of the UK and Canadian governments to the exploitation of corporate residence. It argues that key legislative and administrative responses to international tax avoidance activities, for both outbound and inbound investment, are purportedly based on the acceptance of formal corporate residence yet undermine that concept in an effort to impose tax or refuse treaty relief based on where economic interests actually exist. The responses considered are the application of controlled foreign companies legislation to offshore subsidiaries, the invocation of treaty anti-abuse rules with respect to offshore intermediaries, and the use of overarching general anti-avoidance measures to challenge varied structures that rely on offshore entities. These haphazard anti-avoidance rules are overlaid with revenue authorities' indignation at the motivations that underlie many corporate relocations. It is argued that a more coherent approach would be to focus on the objective reality or unreality of corporate establishment, by reformulating corporate residence in domestic law and tax treaties.
Keywords: Economics Law; International business; International taxation; Multinational enterprises; Resident companies; Tax avoidance; Tax planning; Taxation

The dilemma of national security and international cooperation in outer space: space technology trade and proliferation controls and their impact on global civil space cooperation - Mineiro, Michael (McGill University, 2011)
In this thesis space technology trade and proliferation controls are analyzed, focusing on two substantive issues that illustrate the challenges and opportunities of reform. The first substantive issue examined is the challenge of domestic law and policy reform in light of international regulatory divergence. This issue is examined through a case study of the U.S. commercial communication satellite export control regime. The second issue is the international implications of space technology trade and proliferation control on global civil space cooperation. The unifying demonstration of this doctoral thesis is that States operate in an international legal system that perpetuates a self-justified security dilemma whose basis originates in the sovereign legal right of States to produce, procure, and maintain space technologies of a military nature. As a result, the international legal system governing space technology trade and proliferation creates a tension between perceived national security needs and the benefits of global cooperation.

Fairness in class action settlements - Piché, Catherine (McGill University, 2011)
To be made effective, class action settlements must be negotiated fairly, be perceived as fair and reasonable by the settlement parties such that they agree to their terms and substance, and be characterized as fair, reasonable and adequate by a court at the occasion of a settlement approval hearing. But how is settlement fairness defined, in a collective litigation context? By which process is the evaluation of fairness made and the approval given by the court? What role does the court correspondingly have, in that context? This thesis explores the legal policy and reasoning behind the mandatory judicial approval of class settlements, the process by which it is sought and obtained, the currently relevant factors and indicia of settlement fairness which support all decisions to approve, and the roles of the principal settlement actors, particularly the settlement judge. It suggests hypotheses for reform applicable to these approval processes, roles of the actors and standard of settlement fairness. These hypotheses are tested, for their plausibility, against empirical data obtained from the qualitative interviews of seventeen judges conducted by the author in four target jurisdictions that have similar approaches to class action settlement approvals, and where class action litigation activity is heavy: Quebec, Ontario, British Columbia, and the United States federal courts. Ultimately, the thesis proposes final recommendations for reform of the class action settlement approval procedure.
Identifier : https://escholarship.mcgill.ca/concern/theses/n009w645z
Keywords: Class action; Class action settlement; Settlement parties

South African anti-dumping law and practice : a juridical and comparative analysis of procedural and substantive issues - Sibanda, Omphemetse Stephen (North-West University, 2011)
This thesis addresses issues of anti-dumping law and practice from a critical and juridical analysis position. In particular, the thesis seeks to determine whether the South African anti-dumping regime is compliant with the anti-dumping regime of the World Trade Organization (hereafter WTO), and to consider possible solutions for addressing instances where the South African law is not WTO compatible. The thesis departs from the hypothesis that the WTO merely requires functional equivalence of the implementation of national legislation on anti-dumping, and not the verbatim adoption of WTO jurisprudence and relevant provisions of the Agreement on the Implementation of Article VI of the General Agreement on Tariffs and Trade of 1994 (hereafter URAA), into the legislation of State Parties. Some of the provisions of the URAA are not completely clear, and are cast in convoluted and complicated technical jargon, leaving loopholes that may be justifiably exploited by State Parties. The study in this thesis was achieved through the critical analysis of legislation and relevant legal documents, case law and contemporary literature. The primary research paradigm used in this study is interpretive and analytical, which is the same as qualitative research methodology. The legal comparative research method, with a historical component, also played an important role in this study. The literature study undertaken and the critical analyses made of the South African anti-dumping regime show mixed findings. The South African antidumping regime was found to have both positive aspects and problematic aspects when compared with WTO regulations. Some of the critical areas of the South African anti-dumping regime are WTO compatible whilst others are not. In some areas the South African anti-dumping regime has adopted functionally equivalent provisions to the provisions of the WTO law. However, the practice of the International Trade Administration Commission (ITAC) is sometimes fraught with inconsistencies. The compatibility of the South African anti-dumping system with the WTO regime came close to being examined by the WTO on 1 April 1999 in the dispute of South Africa - Anti-dumping Duties on the Import of Certain Pharmaceutical Products from India based on allegations that the method for calculating normal value used by the ITAC was found to be inconsistent with the URAA. Similarly, the conformity of the procedures and findings of the International Trade and Administration Act (ITAA) in anti-dumping cases came under attack in the cases of Algorax v The International Trade Administration Commission and others, and Scaw v The International Trade Administration Commission and others, respectively. Finally, the thesis ends with recommendations in response to the challenges identified and key submissions made throughout the analysis. Key recommendations include the broadening of the concept of interested parties to include registered trade unions and trade union federations; introducing an explicit and mandatory "public Interests" provision to ensure that South Africa's anti-dumping administration is free from political trappings in the form of the involvement of the Minister of Trade and Industry; introducing the new section 31 bis of the ADR in order to allow the initiation of anti-dumping petitions by a registered trade union or trade union federation; providing procedural guidelines for self-initiation of anti-dumping petitions by the ITAC; increasing transparency in anti-dumping proceedings and enquires; setting realistic time-lines for all anti-dumping processes and ensuring compliance with the same; improving the institutional and functional capacity of the ITAC; amending section 18.3 of the ADR to allow search and seizure operations pursuant to the provisions of the Criminal Procedure Act 51 of 1977 and the Customs Act; having a clear provision on verification visits confidentiality and a clear provision on producer knowledge; introducing a clear provision in the ADR dealing explicitly with zeroing pursuant to Article 2.4.3 (ii) of URAA; and the introduction of duty refund procedures. It is hoped that the recommendations made in this thesis, which are in the form of suggested legislative interventions required to upgrade certain areas of South African anti-dumping law and practice to be fully WTO compliant, will influence the introduction of suitably crafted anti-dumping legislation in South Africa. It is further hoped that the thesis will become an invaluable source of information for practitioners and students, and a critical source on the best practice for the imposition and implementation of anti-dumping measures. Moreover, the thesis will add to the body of academic writing on South African anti-dumping law.
Keywords: Antidumping duties; Dumping (International trade); South Africa

Market access and sustainable development: a legal policy analysis of the market access regime of the least developed countries under the WTO - Tania, Sharmin Jahan (Macquarie University, 2011)
"The main objective of the thesis is to examine whether improved market access for the exports of the least developed countries (LDCs) is a significant means for achieving sustainable development through trade. Further, it aims to examine whether LDCs face challenges in achieving their sustainable development in the existing market access regime... Recognising the specific needs of LDCs, the Preamble to the 'WTO Agreement' calls for positive efforts designed to ensure that LDCs secure a share in the growth in international trade commensurate with the needs of their economic development."
Keywords: Commerce; Developing countries; Exports; Foreign trade regulation; Free Trade; Sustainable development; WTO; World Trade Organization

Essays on policy reforms in trade, investment and taxation - Wagle, Swarnim (Australian National University, 2011)
This thesis consists of three essays on trade, investment, and taxation that are unified by their policy relevance to developing countries. Following an introductory chapter on policy reform, the first essay revisits the institutional determinants of foreign direct investment (FDI) using a comprehensive new data set covering more than 80 countries. It exploits the presence of confirmed zero investment flows between countries to estimate productivity cut-offs of firms that invest abroad profitably. This approach corrects likely biases arising from firm heterogeneity and country selection in a theoretically derived gravity-type model. The analysis finds inward FDI to be highly responsive to cross-country variation in specific institutional provisions, such as arbitration of disputes and legal procedures to establish foreign subsidiaries. The importance of FDI-specific regulations stands out even after controlling for the general quality of institutions. Statutory openness to FDI, however, has no association with actual inflow of investment. The second essay examines cross-national differences in the survival of exports through the lenses of product, industry, and country characteristics. The estimates are derived from a new application of discrete-time models instead of the continuous-time (Cox) models that are standard in trade duration analysis. The examination of exports originating in more than 100 developing countries covering 4000 products over 12 years shows that export flows are much more fragile than suggested by trade theory. Using new measures of product sophistication and export diversification, the paper finds evidence of information and network externalities that aid export survival. Exports concentrated in a few industries or in a narrow range of destination markets exhibit higher rates of death, whereas export concentration within some industries is positively associated with survival, suggesting a synergistic network effect. The probability of export death decreases with proximity from the capital content of products to the national factor endowment, competitive real exchange rate, and bilateral trade preferences. Further, death rates for dynamic subsets of exports like manufactured components and processed food differ from other products, belying the notion that short durations are necessarily a result of poor exporter capabilities. The third essay assesses the revenue implications of coordinated tariff and tax reforms. It is shown for a sample of low-income countries over 25 years that they have had a mixed record of offsetting reductions in trade tax revenue, and that Value-Added Tax (VAT) has, at best, played a limited role. The paper then analyzes the specific case of Nepal, using a unique data set compiled from unpublished customs records of imports, tariffs, and all other taxes levied at the border. It estimates changes to revenue and domestic production associated with two sets of reforms: i) proportional tariff cuts coordinated with a strictly enforced VAT; and ii) proposed tariff cuts under a regional free trade agreement. It is shown that a revenue-neutral tax reform is conditional on the effectiveness with which domestic taxes are enforced. Furthermore, loss of revenue as a result of intra-regional free trade can be minimized through judicious use of Sensitive Lists that still cover "substantially all the trade" as required by Article XXIV of the General Agreement on Tariffs and Trade (GATT).
Keywords: Commercial policy; Fiscal policy; Free Trade; Investments; Taxation